Discharge correction for longitudinal and/or transverse settlements of Parshall flumes - Prasad, Shiv; Rajput, TBS (Journal of Agricultural Engineering, 2006)
Head-discharge relationship of a 7.62 cm Parshall flume were studied under different longitudinal as well as transverse settlements. Discharge measure from the flume were compared with the actual discharges under positive as well as negative settlements. The results indicated that the Parshall Flume accuracy was affected by the degree of settlement in either directions. However, longitudinal settlement affected head-discharge relationship more significantly. When the slope of longitudinal and transverse settlement of the Parshall flume were of opposite type their combined effect on the head-discharge relationship was found to be less than their individual effects and partly compensated each others influence on the flume rating . Based on regression analysis a correction factor was proposed.